Rethinking geopolitics - Black, Jeremy, 1955- (Indiana University Press, 2024)
"In 1904, geopolitical theorist Halford Mackinder delivered a seminal lecture entitled "The Geographical Pivot of History" to a packed house of the Royal Geographical Society in London about the historic changes then taking place on the world stage. Britain was the great power of that historical moment, but its political, military, and economic primacy was under serious challenge from America, Germany, and Russia. Mackinder predicted that the "heartland" of Eastern Europe held the key to global hegemony, and that the struggle for control over this region would be the next great conflict. Ten years later, when an assassin's bullet in Sarajevo launched the world into a calamitous war, Mackinder's analysis proved prescient. As esteemed historian Jeremy Black argues in this timely new volume, the 2020s may be history's next great pivot point. Amid the bloody Russian invasion of Ukraine and the escalating tensions across the Taiwan Strait, the geopolitical balance of power has changed significantly in a very short period. The continued volatility of the global system in the wake of a deadly pandemic exacerbates these tensions. At the same time, the American public remains divided by the question of engagement with the outside world, testing the limits of U.S. postwar hegemony. The time has come for a reconsideration of the 120 years from Mackinder's lecture to now, as well as geopolitics of the present and of the future"--